2004
DOI: 10.1093/nar/gkh233
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a direct Dlx homeodomain target in the developing mouse forebrain and retina by optimization of chromatin immunoprecipitation

Abstract: Understanding homeobox gene specificity and function has been hampered by the lack of proven direct transcriptional targets during development. Dlx genes are expressed in the developing forebrain, retina, craniofacial structures and limbs. Dlx1/Dlx2 double knockout mice die at birth with multiple defects including abnormal forebrain development and decreased Dlx5 and Dlx6 expression. We have successfully applied chromatin immunoprecipitation (ChIP) to identify a direct transcriptional target of DLX homeoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 32 publications
4
78
1
Order By: Relevance
“…For example, the intergenic regions of the Drosophila bithorax complex (BX-C) genes contain cis-regulatory elements that are transcribed, their transcription preceding and regulating activation of abdominal genes Drewell et al, 2002). The evidence that the novel noncoding RNA identified in this study may be implicated in a similar transcriptional regulation of Dlx5 and Dlx6 comes from the finding that the first exon of EST AK032537 overlaps in part with the I56i enhancer element (Zerucha et al, 2000) to which DLX1 and DLX2 proteins bind (Zhou et al, 2004) to regulate Dlx5 and Dlx6 transcription. Moreover, this hypothesis is strengthened by the overlap between mEvf-1 and Dlx5-Dlx6 expression (Anderson et al, 1997b;Eisenstat et al, 1999).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, the intergenic regions of the Drosophila bithorax complex (BX-C) genes contain cis-regulatory elements that are transcribed, their transcription preceding and regulating activation of abdominal genes Drewell et al, 2002). The evidence that the novel noncoding RNA identified in this study may be implicated in a similar transcriptional regulation of Dlx5 and Dlx6 comes from the finding that the first exon of EST AK032537 overlaps in part with the I56i enhancer element (Zerucha et al, 2000) to which DLX1 and DLX2 proteins bind (Zhou et al, 2004) to regulate Dlx5 and Dlx6 transcription. Moreover, this hypothesis is strengthened by the overlap between mEvf-1 and Dlx5-Dlx6 expression (Anderson et al, 1997b;Eisenstat et al, 1999).…”
Section: Discussionmentioning
confidence: 81%
“…AK032537 partially overlaps with enhancer I56i (nucleotides 1-114 of AK032537). Of interest, it has been shown that both DLX1 and DLX2 proteins bind to I56i (Zhou et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin Immunoprecipitation Assays-ChIP was performed under the following conditions as described (17). 1-2 ϫ 10 7 E13.5 ganglionic eminence cells were fixed with 1% paraformaldehyde for 90 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The binding reactions were incubated for 30 min at room temperature. We added unlabeled probes for "cold competition" assays and specific polyclonal DLX1 or DLX2 antibodies for "supershift" assays and polyclonal Secretory Component antibody (Dako, Mississauga, Ontario) to control for nonspecific binding (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation